Ідеал "досконалої людини" у православ'ї - Корольова, І. Є. (НТУ "ХПІ", 2009)
Стаття присвячена аналізу досконалої людини у православ’ї. Розроблена семантика «ідеальної людини», «досконалої людини» та «нової людині» у просторі етико-аксиологічних категорій Нового Заповіту. Використано герменевтичні та концептуально-семантичні методи аналізу релігійно-теологічних текстів християнства. Виявлено зміст морально-етичних категорій в христології.

The article is devoted to the analysis of a perfect man in the Orthodoxy. To outline the appearance of Christ as a perfect man within the limits of the Sainted Letter, with the stressing (accentuation) on the messages of St. Apostle Pavlo, Evangel from St. Matvij and St. Mark. The research novelty is conditioned by the bringing of the germenevtik and conceptually-semantic methods, of the analysis in the religiously-theology texts of Christianity and by the exposure of maintenance of morally-ethical categories in a Christology.
Keywords: філософія; ідеальна людина; нова людина; християнська етика; євангельське світорозуміння; слова; вчинки; обраний народ